Foundations in strategic management - Harrison, Jeffrey S. (South-Western College, 1998)
This book is about: The strategic management process; The external environment; The internal environment and strategic direction; Business strategy; Corporate strategy; Strategy implementation; Strategic control and restructuring; and Strategic challenges for the twenty-first century.